Hierarchical targeted hepatocyte mitochondrial multifunctional chitosan nanoparticles for anticancer drug delivery. (June 2015) - Chen, Zhipeng; Zhang, Liujie; Song, Yang; He, Jiayu; Wu, Li; Zhao, Can; Xiao, Yanyu; Li, Wei; Cai, Baochang; Cheng, Haibo; Li, Weidong
Abstract: The overwhelming majority of drugs exert their pharmacological effects after reaching their target sites of action, however, these target sites are mainly located in the cytosol or intracellular organelles. Consequently, delivering drugs to the specific organelle is the key to achieve maximum therapeutic effects and minimum side-effects. In the work reported here, we designed, synthesized, and evaluated a novel mitochondrial-targeted multifunctional nanoparticles (MNPs) based on chitosan derivatives according to the physiological environment of the tumor and the requirement of mitochondrial targeting drug delivery. The intelligent chitosan nanoparticles possess various functions such as stealth, hepatocyte targeting, multistage pH-response, lysosomal escape and mitochondrial targeting, which lead to targeted drug release after the progressively shedding of functional groups, thus realize the efficient intracellular delivery and mitochondrial localization, inhibit the growth of tumor, elevate the antitumor efficacy, and reduce the toxicity of anticancer drugs. It provides a safe and efficient nanocarrier platform for mitochondria targeting anticancer drug delivery.